(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
The study evaluated the anti-trypanosomal effects of methanolic extracts from the fruit, stem bark, and root of Morinda lucida against Trypanosoma brucei brucei. Each plant part (100 g) was macerated in 1000 mL of methanol for 72 hours. Phytochemical assays revealed the presence of saponins, flavonoids, phenols, tannins, terpenoids, alkaloids, anthraquinone, and cardiac glycosides. Extract yields were 1.81 g (fruit), 2.22 g (root), and 3.71 g (stem bark). Quantitative analysis showed polyphenols, flavonoids, and alkaloids were most abundant in the root. In vitro tests demonstrated concentration-dependent trypanocidal effects, with median lethal concentrations (LC50) of 0.463, 0.406, and 0.664 mg/mL for fruit, root, and stem bark extracts respectively. The anti-infectivity test indicated that extracts inhibited the ability of T. b. brucei to initiate infection in mice. This study suggests that M. lucida extracts possess significant in vitro anti-trypanosomal activity and inhibit infectivity, highlighting their potential as alternative treatments for trypanosomiasis.